Syed Azim Murtaza : As A Reticent Poet (Journal of Namibian Studies : History Politics Culture, 2023)
Azim Murtaza, in his most isolated place , has gently cut the curve of his possibilities along with his age. The imitation of the poets begins to show its colors. In the art of Azim Murtaza, the whole evolution is slowly unfolding and one can feel that he hates the terms of wearing a belt and a clock . He is not just a good lion. He say good ghazals, his poems are not prisoners of his loneliness, his poems are prisoners of the group of his companions, and they fly in the direction of the thoughts. The greatest sorrow of Azim Murtaza, the seeker of the original grief, is that the manifestations of grief are not ready to leave him. It should be that this failed attempt of Azim Murtaza is the most powerful part of his personality and this is the point where he seems to repeat the steps taken by modern poets.